Aislamiento de Salmonella enterica y reactividad serológica a Leptospira interrogans en tlacuaches (Didelphis virginiana) de Yucatán, México - RUIZ-PIÑA, Hugo Antonio (2002)
The presence of Salmonella enterica and serologic evidence of infection by Leptospira interrogans, were detected in the opossum Didelphis virginiana in a semi-urban locality of the Yucatán State, México. Ninety-one opossums were captured during the period April 1996 and May 1998. From a total of 17 feces samples, four Salmonella enterica subsp. enterica serotypes (Sandiego, Newport, Anatum, and Minnesota), and one Salmonella enterica subsp. arizonae serovar O44:Z4,Z23:- were isolated. Some opossums presented mixed infections. From 81 sera samples, four (4.9%) were positive to antibodies to Leptospira serovars pomona and wolfii. Both animals infected with Salmonella enterica and those serologically positive to Leptospira interrogans were captured in peridomestic habitat. Opossums infected with Salmonella enterica, were captured in dry season, and those seropositive to Leptospira interrogans during the rainy season. The implications of infection and reactivity of these zoonotic pathogens in D. virginiana in the Yucatan state are briefly discussed.